Updating the Salivary Gland Transcriptome of Phlebotomus papatasi (Tunisian Strain): The Search for Sand Fly-Secreted Immunogenic Proteins for Humans - Abdeladhim, Maha; Jochim, Ryan C.; Ben Ahmed, Melika; Zhioua, Elyes; Chelbi, Ifhem; Cherni, Saifedine; Louzir, Hechmi; Ribeiro, José M. C.; Valenzuela, Jesus G. (PLOS ONE, 2012)
Introduction Sand fly saliva plays an important role in both blood feeding and outcome of Leishmania infection. A cellular immune response against a Phlebotomus papatasi salivary protein was shown to protect rodents against Leishmania major infection. In humans, P. papatasi salivary proteins induce a systemic cellular immune response as well as a specific antisaliva humoral immune response, making these salivary proteins attractive targets as markers of exposure for this Leishmania vector. Surprisingly, the repertoire of salivary proteins reported for P. papatasi–a model sand fly for Leishmania-vector-host molecular interactions–is very limited compared with other sand fly species. We hypothesize that a more comprehensive study of the transcripts present in the salivary glands of P. papatasi will provide better knowledge of the repertoire of proteins of this important vector and will aid in selection of potential immunogenic proteins for humans and of those proteins that are highly conserved between different sand fly strains. Methods and Findings A cDNA library from P. papatasi (Tunisian strain) salivary glands was constructed, and randomly selected transcripts were sequenced and analyzed. The most abundant transcripts encoding secreted proteins were identified and compared with previously reported sequences. Importantly, we identified salivary proteins not described before in this sand fly species. Conclusions Comparative analysis between the salivary proteins of P. papatasi from Tunisia and Israel strains shows a high level of identity, suggesting these proteins as potential common targets for markers of vector exposure or inducers of cellular immune responses in humans for different geographic areas.